The School of Libanius in Late Antique Antioch - Cribiore, Raffaella (Book collections on Project MUSE., 2007)
This book is a study of the fourth-century sophist Libanius, a major intellectual figure who ran one of the most prestigious schools of rhetoric in the later Roman Empire. He was a tenacious adherent of pagan religion and a friend of the emperor Julian, but also taught leaders of the early Christian church like St. John Chrysostom and St. Basil the Great. Raffaella Cribiore examines Libanius's training and personality, showing him to be a vibrant educator, though somewhat gloomy and anxious by nature. She traces how he cultivated a wide network of friends and former pupils and courted powerful.